Trajetórias de professores de classes multisseriadas: memórias do Ensino Rural em Novo Hamburgo/RS (1940 a 2009) - Souza, José Edimar de (Universidade do Vale do Rio dos Sinos, 2011)
This study approach around multigrade classes teachers memories, building history of rural education (1940-2009), at the region of Lomba Grande, the city of New Hamburg/ RS/Brazil. Memories are analyzed from the social time Halbwachs perspective: when memory allows individuals to take his place in the network of social relations inscribed within the social practice, is crucial to understanding the practice of a group. The research was qualitative, with the methodology of oral history, by semi-structured interviews, and also documentary analysis from written documents (official documents, laws, decrees, images and other printed and manuscripts documents), founded along the course of investigation. Under the frame of Cultural History, the analysis is structured in two dimensions: teaching formations memories and the teaching practices memories. Thus, from the trajectories of this group of teachers, complemented by other empirical data, its possible to understand a significant route of the history of rural local public education, there being three distinct phases: the first time, when processing the constitution of Isolated Schools and a second phase, characterized as the consolidation of Lomba Grande public school, and the third, regarded here as the phase of restructuring rural public school in that place. The formations memories allowed visualize the single master representation atteaching students time. On the other hand, teaching practices memories brings up strategies built by the teachers for their own education, creating forms to qualify the multigrade classes work.
Keywords: Professores rurais; Memórias de professores; Prática docente multisseriada; Ensino rural; Rural teachers; Rural education; Teacher’s memories; Multigrade teaching practices; ACCNPQ::Ciências Humanas::Educação